Species distribution model for Buxbaumia viridis, identifying new areas of presumed distribution in the Czech Republic - Číhal, Lukáš; Fialová, Lucie; Plášek, Vítězslav (Acta musei silesiae : scientiae naturales, 2020)
There is a large number of organisms in nature that are hard to find in the field, and one of these is also a rare bryophyte species, , which can also only be found in a certain part of the year in the production of sporophytes. Using distribution models, however, it is possible to predict the locations which this species is likely to be present at and to focus the field research directly on such sites. Thanks to the presented model, we have succeeded in identifying areas within the Czech Republic with an increased likelihood of its occurrence, even in some areas where no collection of has so far been recorded. With the help of the maps created these locations can be identified with the accuracy of approximately 1 km , making it easier for terrain research and resulting time and often financial expenses. We have also focused on the study of ecological factors that influence the occurrence of the species, and by testing variables from different categories we have come to some agreement with previously published studies. Whilst we have managed to exclude that air pollution has a major role to its occurrence, which has not yet been the subject of any study.